Preemptive and Upfront Plerixafor: Safe and Effective Strategy for Patients Undergoing Autologous Stem Cell transplant and at High Risk for Mobilization Failure - Sheth, Vipul; Jain, Reetu; Gore, Adwaita; Ghanekar, Amit; Saikia, Tapan (Indian Journal of Medical and Paediatric Oncology, 2020)
Introduction: Approximately 10%–30% of patients are unable to collect the minimum number of stem cells to support high-dose chemotherapy and autologous stem cell transplant (hematopoietic stem cell transplantation). Plerixafor alone or in combination with granulocyte colony-stimulating factor (G-CSF) has been shown to significantly increase the CD34 cell collection, especially in patients who failed their initial harvest strategy. This is a retrospective study of 17 preselected patients (relapsed lymphoma and myeloma), who were considered to have high risk of mobilization failure and who had undergone upfront and preemptive plerixafor mobilization. Patients and Methods: The mobilization protocol consisted of G-CSF (10–15 μg/kg) subcutaneously daily for 4 days before the initiation of plerixafor on evening of day 4. The patients then underwent apheresis on day 5. Results: Among 17 patients who underwent apheresis, 16 (93%) yielded the minimum required cell collection of ≥2 × 106 CD34+ cells/kg in a single apheresis session (2 days). Out of these 16 patients, 8 (53%) patients achieved the minimum target dose in a single day. Eight (50%) of all patients achieved the optimum target cell collection in a single apheresis session. Out of these eight patients, five (62%) patients collected optimum yield in a single day. Conclusion: Plerixafor is safe and effective if used upfront and preemptively for patients in whom mobilization of stem cells is considered to be a problem.
Keywords: Autologous stem cell transplant; plerixafor; preemptive upfront